ANALYSIS OF ZEROTIER'S USAGE DURING THE COVID-19 PANDEMIC - Stefanus Eko Prasetyo; Frans Hadinata; Haeruddin Haeruddin (Universitas Internasional Batam, 2022)
During this COVID-19 pandemic, most office employees are required to implement health protocols such as washing hands, wearing masks, and social distancing. The application of health protocols in the world of work can be in the form of Work From Home. Work From Home is one way to implement social distancing to reduce the spread of the coronavirus or COVID-19. In this case, employees find it difficult to access office data. For this reason, secure technology such as VPN is needed to connect the office network to the home network so that every employee can access the data in the office. With the hope that these employees can work productively even though they are not in the office. That technology is ZeroTier. ZeroTier is a technology that allows connecting personal devices and other devices without having to be in a close location. Devices also don't have to be connected to the same network to use ZeroTier. The method used in this research is the Network Development Life Cycle. With the results of the research that ZeroTier's extensive scalability and operating system support are quite varied, it is possible for every end-user who has an internet network to connect to the same ZeroTier server network. That way each end-user can communicate directly like being on a local network such as pinging, file sharing, or printer sharing.